“How I feel in my own body” - Guerra Aguiar, Ines; Saraiva, Joana (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
Introduction: Eating disorders (ED) are currently considered one of the most common chronic disorders in the adolescent population, and their course and outcome are often severe. The aims of this study were to (i) evaluate the presence of psychopathology in an adolescent population with ED; (ii) investigate the association between psychopathology and illness severity; and (iii) investigate if the motivation for self-treatment is associated with the presence of psychopathology and ED severity. Materials and Methods: The sample consisted of 43 adolescent patients aged between 12 and 18 years old attending an Eating Disorders Consultation and with a diagnosis of feeding and eating disorder according to the DSM-5 criteria. Participants completed several questionnaires, including the Youth Self-Report (YSR), the Eating Disorder Examination - Questionnaire (EDE-Q, 4th edition), the Anorexia Nervosa Stages of Change Questionnaire (ANSOCQ), and the Bulimia Nervosa Stages of Change Questionnaire (BNSOCQ). Results: The study group consisted of 42 girls (97.7%) and one boy (2.3%). The mean age was 14.65 years (standard deviation 1.73), and 72.1% were diagnosed with anorexia nervosa. The model used to test if the motivation for self-treatment was associated with the presence of psychopathology and ED severity was statistical significant, but only ED severity (EDE-Q) was a significant predictor. The correlation between YSR results (total score) and EDE-Q total results was also significant. Conclusion: As expected, the model concluded that the more disturbing the eating behavior (indicated by EDE-Q results), the less motivated patients are to treat themselves. Although it was anticipated that greater levels of psychopathology would negatively influence the motivation to change, that was not found in this study.